2017
DOI: 10.1104/pp.17.01388
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional RNA Binding Protein OsTudor-SN in Storage Protein mRNA Transport and Localization

Abstract: The multifunctional RNA-binding protein Tudor-SN plays multiple roles in transcriptional and posttranscriptional processes due to its modular domain structure, consisting of four tandem Staphylococcus nuclease (SN)-like domains (4SN), followed by a carboxyl-terminal Tudor domain, followed by a fifth partial SN sequence (Tsn). In plants, it confers stress tolerance, is a component of stress granules and P-bodies, and may participate in stabilizing and localizing RNAs to specific subdomains of the cortical-endop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 90 publications
0
27
0
Order By: Relevance
“…One is OsTudor-SN (Sami-Subbu et al, 2001;Okita and Choi, 2002;Wang et al, 2008), previously called Rp120, which consists of four tandem staphylococcus nuclease (SN)-like domains (4SN module) followed by a C-terminal region containing a Tudor domain and truncated SN (TSN module). Mutations of OsTudor-SN resulted in mislocalization of both prolamine and glutelin mRNAs (Chou et al, 2017). While the 4SN module exhibits RNA binding activity, the TSN module binds to multiple RNA binding proteins.…”
Section: Rbp-p Is Required For Proper Subcellular Localization Of Botmentioning
confidence: 99%
See 1 more Smart Citation
“…One is OsTudor-SN (Sami-Subbu et al, 2001;Okita and Choi, 2002;Wang et al, 2008), previously called Rp120, which consists of four tandem staphylococcus nuclease (SN)-like domains (4SN module) followed by a C-terminal region containing a Tudor domain and truncated SN (TSN module). Mutations of OsTudor-SN resulted in mislocalization of both prolamine and glutelin mRNAs (Chou et al, 2017). While the 4SN module exhibits RNA binding activity, the TSN module binds to multiple RNA binding proteins.…”
Section: Rbp-p Is Required For Proper Subcellular Localization Of Botmentioning
confidence: 99%
“…While the 4SN module exhibits RNA binding activity, the TSN module binds to multiple RNA binding proteins. The two independent modules likely cooperate in mRNA localization (Chou et al, 2017).…”
Section: Rbp-p Is Required For Proper Subcellular Localization Of Botmentioning
confidence: 99%
“…The interrelatedness of the three RNA transport pathways suggests that they share common trans-factors for targeting to the ER membrane, while glutelin and prolamine pathways require additional factors for selective transport (Chou et al, 2019). Indeed, our studies showed that prolamine and glutelin zipcode sequences bind identical transfactors, Tudor-SN (Chou et al, 2017;Tian et al, 2018, 2019), RBP-P (Chou et al, 2017; Tian et al, 2018, 2019), and RBP-L (Chou et al, 2017;Tian et al, 2018Tian et al, , 2019.…”
Section: Mrna Localization In Plant Cellsmentioning
confidence: 65%
“…This RBP was initially identified as a cytoplasm-localized, cytoskeleton-associated protein in developing rice grains (Sami-Subbu et al, 2001;Wang et al, 2008). It contains four tandem Staphylococcus nuclease domains (4SN module) and a Tudor domain followed by an additional truncated SN domain in the C terminus (Tsn module; Chou et al, 2017). The N-terminal 4SN module directly binds to glutelin and prolamine mRNAs, while the Tsn module possesses the capacity to interact with eight other RBPs (Chou et al, 2017).…”
Section: Nonzipcode Trans-factorsmentioning
confidence: 99%
See 1 more Smart Citation